Method for pickling to induce high grain boundary ionic conduction of proton ceramic electrolyte material and application

CN122638525BActive Publication Date: 2026-10-30INNER MONGOLIA UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611088153.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-30
Estimated Expiration
2046-07-22

AI Technical Summary

Technical Problem

这些方法虽然能够在一定程度上促进致密化,但对粉体表面及晶界前驱区域中已有高阻抗杂质缺乏针对性调控,难以从源头减少杂质相在最终晶界区域的富集

Benefits of technology

第一,本发明针对晶界离子传输受限的根源进行调控。现有方法多依赖烧结温度、保温时间或烧结助剂调节电解质性能,而本发明将调控对象前移至烧结后电解质粉体的表面和晶界前驱区域,可从源头减少高阻抗杂质对最终晶界结构的不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122638525B_ABST
    Figure CN122638525B_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of new energy solid-state electrochemical energy device materials, and discloses a method and application of pickling-induced high-grain-boundary ionic conduction of a proton ceramic electrolyte material. After high-temperature sintering, crushing, ball milling and drying of the proton conductor ceramic electrolyte material are completed, the obtained sintered electrolyte powder is further subjected to pickling-induced treatment, the chemical state of the powder particle surface, the particle edge and the grain boundary precursor area is regulated, the migration and enrichment of high-resistance impurity phases to the grain boundary area in the subsequent electrolyte layer sintering process are reduced, and the continuous transmission capacity of protons at the electrolyte grain boundary is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid-state electrochemical energy device materials technology, and more specifically, to a method for inducing and enhancing grain boundary ion transport in proton ceramic battery electrolytes. More specifically, this invention relates to powder interface regulation, grain boundary structure optimization, and ion transport performance improvement of proton conductor ceramic electrolyte materials, applicable to solid-state electrochemical energy conversion devices such as reversible proton ceramic batteries. Background Technology

[0002] Proton ceramic batteries are a new type of solid-state electrochemical energy device that uses proton-conducting ceramic materials as electrolytes. These batteries use protons as the primary charge carriers and, compared to traditional oxygen-ion-conducting solid oxide batteries, feature lower ion migration activation energy, relatively lower operating temperature, higher energy conversion efficiency, and faster start-up speed. They have significant application value in fields such as medium-temperature fuel cells, hydrogen electrolysis, ammonia conversion and utilization, and reversible electrochemical energy conversion.

[0003] In proton ceramic batteries, the electrolyte layer is a core component determining device performance. The electrolyte layer needs to simultaneously achieve effective isolation between fuel gas and oxidizing gas, efficient proton conduction, and effective blocking of electron transport. The densification degree, grain boundary structure, and ion transport capability of the electrolyte material directly affect the battery's ohmic impedance, power output, and long-term operational stability. Among these, grain boundary regions, as the interface between grains, are often key weak points affecting actual ion transport performance. Therefore, constructing grain boundary ion transport channels with low impedance, high continuity, and high stability is an important technical direction for improving the overall performance of proton ceramic batteries.

[0004] BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Perovskite-type proton conductor ceramic electrolyte materials possess high proton conductivity and good electrochemical performance, making them representative high-performance electrolyte materials in proton ceramic batteries. However, during the preparation, powder processing, and storage of these electrolyte materials, a certain amount of non-main phase impurities, surface reaction products, residual oxides, or amorphous phases are easily present on the powder surface or in the particle contact area. Although the overall content of these substances is limited, they are usually distributed on the powder particle surface, particle edges, or in the contact area of ​​aggregates, and have a significant impact on the subsequent sintering densification behavior of the electrolyte layer and the grain boundary ion transport characteristics.

[0005] When electrolyte powder containing surface impurities or interface residues is further used in the preparation of electrolyte layers, these impurity phases are prone to migration, segregation, or redistribution during high-temperature processes, and accumulate in the grain boundary regions of the final electrolyte layer. On the one hand, impurity phases weaken the effective contact between particles, hinder grain boundary movement and sintering densification processes, resulting in residual porosity or local structural inhomogeneity in the electrolyte layer. On the other hand, high-resistivity substances such as carbonates, hydroxides, amorphous phases, and unreacted oxides may form continuous or semi-continuous blocking phases at grain boundaries, increasing the proton migration barrier across grain boundaries and reducing grain boundary conductivity and total electrolyte conductivity.

[0006] For proton ceramic batteries, the intrinsic proton conductivity of the electrolyte bulk phase does not fully represent the actual ion transport performance of the device. If high-resistivity impurity phases, discontinuous interfaces, or local transport barriers exist in the grain boundary regions, even if the electrolyte grains have good proton conductivity, the overall ohmic impedance of the battery will still increase significantly, thus limiting power output and operational stability under medium and low temperature conditions. Therefore, the structural state and chemical environment of the electrolyte grain boundary regions are among the key factors affecting the performance of proton ceramic batteries.

[0007] In existing technologies, to improve the ion transport performance of proton ceramic electrolytes, methods such as optimizing the sintering process, increasing the sintering temperature, extending the holding time, controlling the powder particle size, adjusting the sintering atmosphere, or introducing sintering aids are commonly used. These methods can promote electrolyte layer densification to some extent, but their effects are mainly concentrated on the sintering process itself, and they are insufficient to fully eliminate the adverse effects of high-resistivity impurities already present on the powder surface and grain boundary precursor regions on the final grain boundary transport performance. Furthermore, excessively high sintering temperatures may cause Ba volatilization, component segregation, or abnormal grain growth; the introduction of sintering aids may also form new second phases or impurity phases at grain boundaries, thereby disrupting the continuity of grain boundary ion transport.

[0008] Therefore, it is necessary to propose a technical solution for enhancing grain boundary ion transport in proton ceramic battery electrolytes. This solution should be able to effectively control the surface state of the electrolyte powder and the grain boundary precursor region, reduce the enrichment of high-resistivity impurity phases in the final electrolyte grain boundary region, lower the resistance to proton migration across grain boundaries, and construct a cleaner, more continuous, and stable grain boundary ion transport channel. This will improve the electrolyte grain boundary conductivity, total conductivity, and the output performance and operational stability of the proton ceramic battery.

[0009] Against this backdrop, existing proton ceramic battery electrolyte materials mainly suffer from limited ion transport at grain boundaries during practical preparation and application. Although perovskite-type proton conductor ceramic electrolyte materials possess good proton conductivity, their actual electrochemical performance is often limited by the structural state and chemical environment of the grain boundary regions, making it difficult to fully realize the intrinsic advantages of the material in terms of total electrolyte conductivity.

[0010] First, after high-temperature sintering, pulverization, ball milling, drying, and subsequent storage, existing electrolyte powders may still contain residues such as non-main phase impurities, surface reaction products, incompletely reacted oxides, or amorphous phases on the particle surface and in the particle contact area. Since these areas are closely related to the grain boundary formation location during the subsequent electrolyte layer sintering process, these residues can easily become an important source of high-resistivity phases at grain boundaries.

[0011] Secondly, during the subsequent sintering of the electrolyte layer, the aforementioned surface residues are prone to migration, segregation, or redistribution, and accumulate in the final electrolyte grain boundary region. This process weakens the effective contact between particles, hinders sintering densification, and increases the risk of residual porosity and local structural inhomogeneity. At the same time, high-resistivity impurity phases may also form continuous or semi-continuous transport barrier layers at the grain boundaries, increasing the proton migration barrier across grain boundaries and reducing grain boundary conductivity and total electrolyte conductivity.

[0012] Furthermore, existing improvement methods mostly focus on optimizing the sintering process, such as increasing the sintering temperature, extending the holding time, controlling the powder particle size, or introducing sintering aids. While these methods can promote densification to some extent, they lack targeted control over high-resistivity impurities already present on the powder surface and in the grain boundary precursor region, making it difficult to reduce the enrichment of impurity phases in the final grain boundary region from the source.

[0013] Furthermore, existing sintering strengthening methods may introduce new problems. Excessively high sintering temperatures can lead to Ba volatilization, component segregation, or abnormal grain growth; prolonged holding time increases energy consumption and exacerbates element migration; sintering aids may introduce new second phases or impurity phases into grain boundary regions, thereby disrupting the continuity of ion transport at grain boundaries. Therefore, relying solely on sintering process control is insufficient to simultaneously achieve electrolyte densification, grain boundary purification, and enhanced ion transport.

[0014] In summary, the main problem with the existing technology is that there is a lack of a technical means to effectively control the surface state of the electrolyte powder and the grain boundary precursor region after sintering. This leads to the easy accumulation of high-resistivity impurity phases in the final electrolyte grain boundary region, hindering proton migration across grain boundaries, which in turn causes an increase in electrolyte ohmic impedance, a decrease in grain boundary conductivity, and limitations on battery output power and long-term stability. Summary of the Invention

[0015] In view of this, the present invention provides a method and application for acid-washed induced high grain boundary ion conduction proton ceramic electrolyte materials. The core design element is as follows: after the proton conductor ceramic electrolyte material has undergone high-temperature sintering, pulverization, ball milling, and drying, the resulting sintered electrolyte powder is further subjected to an induced treatment to regulate the chemical state of the powder particle surface, particle edges, and grain boundary precursor regions. This reduces the migration and enrichment of high-resistivity impurity phases into the grain boundary regions during subsequent electrolyte layer sintering, thereby enhancing the continuous transport capability of protons at the electrolyte grain boundaries.

[0016] One objective of this invention is to provide a method for developing a proton-ceramic electrolyte material with high grain boundary ion conduction induced by acid washing, comprising the following steps:

[0017] a. The sintered electrolyte powder is added to an acid-induced solution, and after stirring and dispersing, a suspension system containing the electrolyte powder is obtained; wherein... The sintered electrolyte powder is: BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The electrolyte powder was sintered at 1400℃ for 5 hours; the acid-inducing solution was a weak acid aqueous solution. b. The suspension system containing electrolyte powder is separated into solid and liquid phases to obtain electrolyte powder. The electrolyte powder is then subjected to multi-stage purification, drying and dispersion treatment to obtain induced activated electrolyte powder, namely, proton ceramic electrolyte material with high grain boundary ion conduction induced by acid washing.

[0018] Preferably, in step a, the concentration of the acid in the acid-inducing solution is 0.5-1 vol.

[0019] Preferably, the acid solution is nitric acid.

[0020] Preferably, in step a, the solid-liquid ratio of the sintered electrolyte powder to the acid-induced solution is 20g:100mL.

[0021] Preferably, in step a, the stirring and dispersing time is 1.5-5 minutes.

[0022] Preferably, in step b, the solid-liquid separation includes, but is not limited to, settling, decantation, centrifugation, or filtration.

[0023] Preferably, in step b, the multi-stage purification process involves repeated dispersion, washing, settling, and separation using ultrapure water or deionized water until the washing solution is nearly neutral.

[0024] The second objective of this invention is to provide an application of a proton ceramic electrolyte material with high grain boundary ion conduction induced by acid washing, for use in preparing the electrolyte layer of a proton ceramic battery.

[0025] This invention is mainly used for interface regulation and performance improvement of proton ceramic battery electrolyte materials, and is particularly suitable for improving the grain boundary ion transport performance of perovskite-type proton conductor ceramic electrolyte powder in the subsequent electrolyte layer preparation process.

[0026] This invention can be used to regulate the chemical state of the electrolyte powder surface and grain boundary precursor region, reduce the adverse effects of high-resistivity impurities on subsequent sintering densification and grain boundary ion migration, and reduce the enrichment of impurity phases in the final electrolyte grain boundary region, thereby constructing a cleaner, continuous, and stable grain boundary ion transport channel. Through the above effects, the grain boundary impedance of the electrolyte layer can be effectively reduced, and the grain boundary conductivity and total electrolyte conductivity can be improved.

[0027] This invention can also be used to prepare proton ceramic battery electrolyte layers with low ohmic impedance, high density, and high proton conductivity. The electrolyte powder processed using this invention can serve as a key material for preparing electrolyte layers in proton ceramic fuel cells, proton ceramic electrolyzers, and reversible proton ceramic batteries, helping to improve the battery's power output, energy conversion efficiency, and operational stability under operating conditions.

[0028] This invention applies to BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ This invention, using barium-containing perovskite-type proton conductor ceramic electrolyte materials, can also be applied to other proton conductor ceramic electrolyte systems that suffer from grain boundary transport limitations. Through this invention, electrolyte material processing solutions and technological foundations can be provided for the fabrication of high-performance, high-reliability proton ceramic batteries and related solid-state electrochemical energy conversion devices.

[0029] During the sintering, pulverizing, ball milling, drying and storage of existing proton ceramic battery electrolyte powder, high-resistivity impurities or surface reaction products are easily present on the powder surface and in the grain boundary precursor region. During the subsequent electrolyte layer sintering process, these impurities tend to migrate and accumulate in the grain boundary region, leading to increased grain boundary impedance, hindered proton migration across grain boundaries, decreased total electrolyte conductivity, and further limiting the power output and operational stability of the proton ceramic battery.

[0030] This invention involves inducing the electrolyte powder obtained after high-temperature sintering, pulverizing, ball milling, and drying of the electrolyte material. The inducing liquid acts on high-resistivity impurities or surface reaction products on the surface, edges, and grain boundaries of the powder particles, reducing the likelihood of these impurities accumulating in the grain boundary regions during subsequent sintering, thereby enhancing the ion transport capacity of the electrolyte grain boundaries.

[0031] As can be seen from the above technical solution, compared with the prior art, the present invention has at least the following beneficial effects: First, this invention addresses the root cause of restricted ion transport at grain boundaries. Existing methods often rely on sintering temperature, holding time, or sintering aids to adjust electrolyte performance, while this invention shifts the control focus forward to the surface of the sintered electrolyte powder and the grain boundary precursor region, thereby reducing the adverse effects of high-resistivity impurities on the final grain boundary structure from the source.

[0032] Second, this invention can reduce grain boundary impedance and improve electrolyte conductivity. Through induction treatment and subsequent purification, the enrichment of high-impedance impurity phases in the final electrolyte grain boundary region can be reduced, the proton cross-grain boundary migration barrier can be lowered, and a cleaner and lower-impedance grain boundary ion transport channel can be formed, thereby improving grain boundary conductivity and total electrolyte conductivity.

[0033] Third, this invention establishes a reasonable parameter window for induction treatment. Experiments show that the effect of induction treatment does not continuously increase with the increase of acid addition or the extension of treatment time, but rather there exists an optimal parameter range. Specifically, when using 0.5 mL of acid solution and treating for 3 min, the electrolyte powder exhibits the highest conductivity, indicating that this condition can achieve a better balance between surface impurity control and the stability of the main crystal phase.

[0034] Fourth, the process conditions of this invention are mild and its applicability is strong. This method does not rely on excessively high sintering temperatures or additional sintering aids, which can reduce the risks of element volatilization, component segregation, abnormal grain growth, and the introduction of foreign second phases, making it suitable for BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ This material contains barium perovskite-type proton conductor ceramic electrolytes and can provide an effective technical solution for the preparation of electrolyte layers in high-performance proton ceramic batteries.

[0035] In summary, this invention can effectively solve the problems of high-impedance impurity accumulation at grain boundaries and limited proton transport across grain boundaries in existing proton ceramic battery electrolyte materials, and helps to improve the ion transport capability at electrolyte grain boundaries, battery power output and operational stability. Attached Figure Description

[0036] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.

[0037] Figure 1 This is a flowchart illustrating the preparation process of the acid-washed electrolyte powder and the full battery of this invention.

[0038] Figure 2XRD patterns of electrolyte powders under different pickling concentrations and times.

[0039] Figure 3 This is a SEM image of the electrolyte powder before pickling.

[0040] Figure 4 This is a SEM image of the electrolyte powder after acid washing with 0.5 mL for 3 min.

[0041] Figure 5 The particle size distribution diagrams are shown for untreated electrolyte powder and electrolyte powder treated with 0.5 mL for 3 min.

[0042] Figure 6 The conductivity diagram shows the electrolyte powder treated with different acid concentrations and times.

[0043] Figure 7 This is a SEM image of the surface of a full cell that has not been acid-washed.

[0044] Figure 8 The image shows the surface SEM image of the full cell after acid washing with 0.5 mL for 3 min.

[0045] Figure 9 The IPV curve of the full cell after acid washing treatment.

[0046] Figure 10 This is a DRT analysis diagram of the impedance of the full cell after acid washing.

[0047] Figure 11 The IPV curves are for full cells that have not undergone acid washing treatment.

[0048] Figure 12 This is a comparison chart of the power density of the full cell before and after acid washing treatment. Detailed Implementation

[0049] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0050] The embodiments of the present invention include the acquisition of electrolyte powder after sintering, induction treatment and parameter screening, solid-liquid separation and multi-stage purification, stabilization post-treatment, and preparation of electrolyte layer and proton ceramic battery.

[0051] (1) Obtaining electrolyte powder after sintering First, a proton ceramic battery electrolyte material is prepared. The electrolyte material selected is a perovskite-type proton conductor ceramic electrolyte material. Considering BaZr... 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ BaZr possesses high proton conductivity, good electrochemical performance, and a foundation for application in proton ceramic batteries, thus making it a promising candidate for proton-ceramic batteries. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ As an electrolyte material, it is used for subsequent induction treatment and grain boundary ion transport enhancement research.

[0052] In the specific preparation process, following the generally accepted preparation methods in this field, BaCO3, ZrO2, CeO2, Y2O3, and Yb2O3 are weighed as raw materials according to the target stoichiometric ratio. These raw materials are mixed with a dispersion medium and then ball-milled to ensure thorough and uniform mixing of the components. The mixture is then dried, ground, and shaped, followed by high-temperature sintering to form the target electrolyte ceramic material. After sintering, the resulting material is pulverized, hand-milled, ball-milled, and dried to obtain the sintered electrolyte powder.

[0053] The target of the induction treatment in this invention is electrolyte powder that has already formed the target main crystalline phase and has undergone crushing, ball milling, and drying, rather than the original mixed powder that has not undergone sintering reaction. By first forming the target electrolyte main phase and then performing subsequent induction treatment, the surface of the powder and the grain boundary precursor region can be further controlled while maintaining the main crystalline phase of the electrolyte.

[0054] (2) Induction treatment and parameter screening The sintered electrolyte powder is added to an induction solution for induction treatment. The induction solution acts on high-resistivity impurities or surface reaction products on the surface of the electrolyte powder particles, particle edges, and in the contact area of ​​agglomerates, causing them to undergo selective transformation, dissolution, desorption, or migration.

[0055] The induction solution is preferably a weakly acidic aqueous solution, more preferably a dilute nitric acid aqueous solution. The amount of acid added and the treatment time of the induction solution can be adjusted according to the composition of the electrolyte powder, the content of impurities on the powder surface, and the dispersion state. The control principle of the induction treatment is to maintain the stability of the main crystal phase structure of the electrolyte while effectively controlling the high impedance impurities on the powder surface and in the grain boundary region.

[0056] In this invention, the amount of acid added in the induction solution and the induction treatment time were systematically screened. Specifically, 0.5-1.0 mL of acid was added to 100 mL of ultrapure water to prepare the induction solution, and the induction treatment time was controlled within the range of 1.5-5 min for comparative experiments. The experimental results show that the amount of acid added in the induction solution and the induction treatment time have a significant impact on the subsequent improvement of the conductivity of the electrolyte powder, and the conductivity does not increase monotonically with the increase of acid added or the extension of treatment time, but shows a clear optimal parameter window.

[0057] When the acid dosage is too low or the induction treatment time is too short, the induction solution is insufficient in controlling high-resistivity impurities, surface reaction products, and residues in the grain boundary precursor region on the powder surface. After the electrolyte layer is sintered, localized impurity enrichment or grain boundary transport obstruction may still exist, resulting in limited improvement in conductivity. When the acid dosage is too high or the induction treatment time is too long, the degree of surface reaction is enhanced, but this may lead to excessive surface reaction, localized compositional deviation, or unstable powder surface conditions, which is detrimental to the subsequent formation of continuous and stable grain boundary ion transport channels. Therefore, excessively high acid dosage or excessively long treatment time will also lead to a decrease in the conductivity improvement effect.

[0058] In the parameter screening above, the electrolyte powder exhibited the highest conductivity when the induction solution was prepared with 0.5 mL of acid and treated for 3 min. This result indicates that the addition amount of 0.5 mL of acid and the induction treatment time of 3 min can achieve a better balance between surface impurity control and electrolyte main phase structure stability. This is beneficial for reducing the enrichment degree of high-resistivity impurity phases in the grain boundary region of the subsequent electrolyte layer and promoting the formation of cleaner, continuous, and low-resistivity grain boundary ion transport channels.

[0059] For BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder can be induced by adding 0.5 mL of acid to 100 mL of ultrapure water to prepare an induction solution. This solution is then used to induce the sintered, ball-milled, and dried electrolyte powder for a preferred treatment time of 3 minutes. The electrolyte powder treated under these conditions can be used to prepare proton ceramic battery electrolyte layers with low grain boundary impedance and high conductivity.

[0060] (3) Solid-liquid separation and multi-stage purification After the induction treatment, the suspension system containing electrolyte powder is subjected to solid-liquid separation to remove the liquid phase containing impurity ions, soluble salts, and reaction products. Solid-liquid separation methods can include static sedimentation, decantation, centrifugation, filtration, or other methods suitable for ceramic powder processing.

[0061] After solid-liquid separation, the obtained electrolyte powder undergoes multi-stage purification. This multi-stage purification preferably involves repeated dispersion, washing, settling, and separation using ultrapure water or deionized water until the washing solution is nearly neutral. This multi-stage purification further removes residual induction liquid, soluble impurity ions, and induced reaction products from the powder surface, preventing residual ions from re-entering the grain boundary region and forming new high-resistivity phases during subsequent sintering. During the multi-stage purification process, the stability of the main phase structure and the processability of the electrolyte powder should be maintained while effectively removing induction residues.

[0062] (4) Post-stabilization treatment The multi-stage purified electrolyte powder is dried and dispersed to obtain induced-activated electrolyte powder. Drying methods include forced-air drying, vacuum drying, or other methods suitable for ceramic powders. After drying, the powder can be further processed by hand milling, low-energy ball milling, sieving, or dispersion to restore a uniformly dispersed state and meet the requirements for subsequent molding and sintering.

[0063] After stabilization treatment, the content of high-resistivity impurities on the surface of the obtained electrolyte powder is reduced, the particle surface state is more stable, and the grain boundary precursor region is cleaner, which is conducive to the formation of a continuous, dense and low-resistivity grain boundary structure during the subsequent electrolyte layer sintering process.

[0064] (5) Preparation of electrolyte layer and proton ceramic battery The induced activated electrolyte powder is used to prepare the electrolyte layer of a proton ceramic battery. The electrolyte layer can be prepared by casting, dry pressing, isostatic pressing, screen printing, slurry coating, scraping, or other ceramic forming methods.

[0065] In the specific preparation process, the induced activated electrolyte powder is mixed with an organic solvent system composed of ethanol and 2-butanone, and dispersants, binders, and plasticizers are added. After ball milling, a uniformly dispersed electrolyte slurry with suitable rheological properties is obtained. Subsequently, a raw electrolyte film is prepared using a casting molding process. After drying, the raw film is composited with an anode support and sintered at 1480℃ for 5 hours to obtain a dense anode support half-cell.

[0066] Based on the obtained half-cell, Ba(Gd) 0.8 La 0.2 Co2O 6-δ (BGLC) cathode paste is uniformly coated on the surface of the half-cell and dried to form a cathode layer with a thickness of about 15 μm. Subsequently, the assembled cell is interfacially co-sintered at 1000 °C for 3 h in air atmosphere to form a continuous and stable porous-dense composite interface structure between the cathode layer and the electrolyte layer, and finally obtains a proton ceramic full cell.

[0067] Because the content of high-resistivity impurities on the surface of the induced-activated electrolyte powder is reduced, the degree of migration and enrichment of impurity phases towards the grain boundary region is decreased during the subsequent sintering of the electrolyte layer, reducing the possibility of forming continuous or semi-continuous blocking phases at the grain boundaries. Therefore, the resulting electrolyte layer can form cleaner, more continuous, and more stable grain boundary ion transport channels, thereby reducing grain boundary impedance and improving grain boundary conductivity and total electrolyte conductivity.

[0068] Example 1 like Figure 1 As shown, this embodiment provides a method for inducing enhanced grain boundary ion transport in proton ceramic battery electrolytes. This method uses BaZr... 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The proton conductor ceramic electrolyte powder is the target material. After the electrolyte material forms the target main crystalline phase, the sintered powder is subjected to acid washing and induction treatment to regulate the chemical state of the powder particle surface, particle edge and grain boundary precursor region, and reduce the adverse effects of high impedance residues on the formation of electrolyte grain boundaries and proton migration across grain boundaries during subsequent sintering.

[0069] (1) According to BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ BaCO3, ZrO2, CeO2, Y2O3, and Yb2O3 were weighed out according to stoichiometric ratios as raw materials. These raw materials were ball-milled, dried, and ground, then placed in a high-temperature furnace and sintered at 1400℃ for 5 h to obtain BaZrO3. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte sintered body. Subsequently, the obtained electrolyte sintered body was subjected to crushing, hand milling, ball milling and drying processes to obtain sintered electrolyte powder. The sintered electrolyte powder has formed a perovskite-type electrolyte main crystalline phase. The subsequent acid washing-induced treatment mainly targets the powder surface and grain boundary precursor regions for regulation, rather than treating the unreacted original mixed powder.

[0070] (2) Take 100 mL of ultrapure water, add 0.5-1 mL of acid solution to it, and stir evenly to obtain the pickling induction solution. Weigh 20 g of the above sintered electrolyte powder and add it to the pickling induction solution. Treat it under stirring conditions for 1.5-5 min to ensure that the pickling induction solution fully contacts the powder particle surface, particle edge and inter-particle contact area.

[0071] The amount of acid and the stirring time can be selected from any value within the range. This invention uses 0.5 mL and 1 mL of acid as examples, and 1.5 min, 3 min and 5 min of processing time as examples.

[0072] (3) After the treatment, the suspension was allowed to settle and the supernatant was removed. Then, about 300 mL of ultrapure water was added to redisperse, wash, settle, and separate the settled electrolyte powder. The washing steps were repeated 4 to 5 times until the supernatant was nearly neutral. After washing, the resulting powder was dried and lightly ground to obtain the acid-induced BaZr. 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Electrolyte powder.

[0073] BaZr after acid washing and induction treatment 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Full batteries were prepared using electrolyte powder, and their electrochemical performance was verified.

[0074] The acid-washed electrolyte powder was mixed with ethanol, 2-butanone, dispersant (triethanolamine), binder (polyvinyl butyral), and plasticizer (polyethylene glycol and dibutyl phthalate). The mass ratio of electrolyte:ethanol:2-butanone:dispersant:binder:plasticizer was 20:25:10:1:2:2. After ball milling, a uniformly dispersed electrolyte slurry was prepared. Subsequently, an electrolyte preform film was prepared using a casting process. The obtained electrolyte preform film was pressed with an anode support and sintered at 1480℃ for 5 h to obtain an anode-supported half-cell. Then, Ba(GdO2) was coated onto the electrolyte surface of the half-cell. 0.8 La 0.2 Co2O 6-δ The cathode paste was used to form a cathode layer with a thickness of about 15 μm, and then co-sintered in air at 1000 °C for 3 h to obtain a proton ceramic full cell.

[0075] Figure 2 The X-ray diffraction patterns of electrolyte powders under different acid-induced treatment conditions are shown. No new phases were found to be generated before and after acid washing, and the structure did not change, indicating that the structure of the electrolyte material was not altered before and after acid washing.

[0076] Depend on Figure 2As can be seen, the main diffraction peak positions of the untreated sample 1711, the 0.5 mL 3 min treated sample, and the 1 mL 5 min treated sample are basically consistent, and no obvious new impurity phase diffraction peaks appear. In the magnified images, the main peak positions around 29° are basically consistent for all samples, indicating that the acid-washed induced treatment did not cause significant damage to the main crystalline phase structure of the electrolyte. This result shows that the acid-washed induced treatment conditions used in this example are relatively mild and can maintain the BaZr... 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Based on the stability of the main crystalline phase of the electrolyte, the surface of the powder and the precursor region of the grain boundary are effectively controlled.

[0077] Figure 3 and Figure 4 The images show the SEM morphology of the electrolyte powder before and after acid-inducing treatment. As can be seen from the figures, both the powder and the untreated powder maintained an irregular granular morphology, with no obvious particle collapse, severe corrosion, or destruction of the main particle structure observed. Compared to the untreated powder, the powder particles treated with 0.5 mL of acid for 3 min showed a more porous and rougher surface, clearer particle boundaries and interparticle pores, and reduced deposits on the surface of some agglomerated particles. This morphological change indicates that the acid-inducing treatment mainly acts on the surface and edge regions of the powder particles, helping to reduce the adverse effects of surface residues or high-resistivity deposits on the subsequent crystal boundary formation process, thus providing a structural basis for the formation of a cleaner and more continuous grain boundary contact interface.

[0078] Figure 5 This shows the particle size distribution of the electrolyte powder before and after acid washing-induced treatment. Figure 5 It can be seen that the D(0.1) and D(0.5) values ​​of the powder before and after treatment are basically the same, with D(0.1) being approximately 1.7 μm and D(0.5) being approximately 3.2 μm, indicating that the acid-induced treatment did not significantly change the particle size distribution of small-diameter particles and the main particles in the powder. The D(0.9) of the sample after acid washing increased from approximately 8.2 μm in the untreated sample to approximately 16.6 μm, indicating an increase in the proportion of large-sized particles or secondary agglomerates. This change is mainly related to the change in the surface state of the powder after acid washing and the re-agglomeration of particles during washing and drying, and does not represent a significant increase in the size of the electrolyte main particles. Overall, the acid-induced treatment has little effect on the main particle size of the powder, mainly changing the distribution of large-diameter ends and the agglomeration state of the powder.

[0079] Comparative Example 1 The only difference between this comparative example and Example 1 is that the electrolyte powder after sintering in step (1) is used as the comparison sample.

[0080] Figure 6The conductivity test results of electrolyte powder under different acid washing induction treatment conditions are shown.

[0081] Conductivity Testing: First, different types of half-cells were prepared using powders with different treatments as raw materials via a casting method. Then, the resulting half-cells were placed in a hydrogen atmosphere for electrochemical impedance spectroscopy testing, and their ohmic resistance was obtained based on the test results. Finally, the conductivity was calculated using the formula... σ = D / (SR) Calculate the electrolyte conductivity, where D is the electrolyte thickness, S is the actual active area, and R is the actual ohmic resistance.

[0082] Depend on Figure 6 It is evident that the 1711 sample without acid-induced treatment exhibited the lowest conductivity within the tested temperature range. This indicates that the untreated powder may still be affected by surface residues, impurity phases, or high-resistivity components in the grain boundary precursor region during subsequent molding and sintering, thus limiting its overall ion transport capacity. After treatment under different acid-induced conditions, the conductivity of the samples improved to varying degrees, with the 0.5 mL 3 min treatment showing the highest conductivity across the entire tested temperature range. This result demonstrates that this treatment condition achieves a better balance between controlling surface residues and stabilizing the electrolyte's bulk structure, resulting in cleaner and more continuous grain boundaries formed during subsequent sintering. This reduces the resistance to proton migration across grain boundaries and improves the electrolyte's grain boundary ion transport capacity.

[0083] Figure 7 and Figure 8 The images show the SEM morphology of the surfaces of full cells prepared from untreated and acid-treated electrolyte powders, respectively. The untreated sample exhibits numerous fine particulate deposits on its surface, densely distributed on the grain surface and near grain boundaries, indicating that the untreated electrolyte may still have surface residues or localized agglomerates after sintering. In contrast, the full cell prepared using the powder treated with 0.5 mL for 3 min of acid washing exhibits a smoother and cleaner surface, clearer grain contours, and a significant reduction in surface particulate deposits. This result further demonstrates that acid washing can mitigate the adverse effects of residues on the powder surface and grain boundary precursor regions on electrolyte grain boundary formation, resulting in more continuous and stable electrolyte grain boundaries after sintering.

[0084] Figure 9 The IPV curve of the full cell after acid washing is obtained. Half cells are prepared by casting using the treatment material with the highest conductivity. Then, cathode paste is coated on the electrolyte side and sintered to form a full cell. The cells are then tested on the assembled test tube. The fuel electrode uses 3% hydrogen permeate and the oxygen electrode uses static air as the oxidant. The IPV relationship is measured using an electron load.

[0085] Figure 10 The DRT analysis results show that the impedance contribution of the battery in the high-frequency and short relaxation time regions decreased after acid-washed induced treatment, indicating a reduction in resistance related to electrolyte ohmic loss and rapid ion transport processes. This result demonstrates that acid-washed induced treatment can improve the ion transport channels at electrolyte grain boundaries, reduce the proton transgrain migration barrier, accelerate ion transport kinetics, and thus improve the output performance of the full cell.

[0086] Figure 11 The IPV curve for the untreated full cell was obtained using the same method as... Figure 9 The same testing method.

[0087] Furthermore, by Figure 12 The power density comparison results show that the peak power density of the full cell after acid washing-induced treatment is significantly higher than that of the untreated sample at all test temperatures. At 700℃, 650℃, 600℃, 550℃, and 500℃, the peak power density of the acid-washed sample is 2689 mW cm⁻¹. -2 1909mW cm -2 1265mW cm -2 774mWcm -2 and 300mW cm -2 The peak power density of the untreated sample at the same temperature was 1187 mW / cm². -2 961mWcm -2 659mW cm -2 329mW cm -2 and 139mW cm -2 Therefore, it can be seen that using the electrolyte powder after acid washing and induction treatment in this embodiment to prepare a full cell can increase the overall peak power density of the full cell by about 2 times, indicating that this method can stably improve the performance of proton ceramic batteries over a wide operating temperature range.

[0088] In summary, this embodiment demonstrates that for sintered BaZr... 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ Acid washing induction treatment of electrolyte powder for 0.5 mL for 3 min can effectively regulate the state of the powder surface and grain boundary precursor region while maintaining the stability of the bulk crystalline structure of the electrolyte. This reduces the adverse effects of high-resistivity residues on grain boundary formation and ion migration during subsequent sintering. This treatment reduces the ion transport resistance at electrolyte grain boundaries, accelerates proton cross-grain boundary transport kinetics, and significantly improves the power output performance of proton ceramic full cells.

[0089] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for acid-washed proton-ceramic electrolyte materials with high grain boundary ion conduction, characterized in that, Includes the following steps: a. The sintered electrolyte powder is added to an acid-induced solution, and after stirring and dispersing, a suspension system containing the electrolyte powder is obtained; wherein... The sintered electrolyte powder is: BaZr 0.1 Ce 0.7 Y 0.1 Yb 0.1 O 3-δ The electrolyte raw material was sintered at 1400℃ for 5 hours, and then crushed, hand-milled, ball-milled and dried to obtain sintered electrolyte powder; the acid-inducing solution was a weak acid aqueous solution. b. The suspension system containing electrolyte powder is separated into solid and liquid phases to obtain electrolyte powder. The electrolyte powder is then subjected to multi-stage purification, drying and dispersion treatment to obtain induced activated electrolyte powder, namely, proton ceramic electrolyte material with high grain boundary ion conduction induced by acid washing. In step a, the concentration of acid in the acid-inducing solution is 0.5-1 vol%. In step a, the stirring and dispersion time is 1.5-5 minutes; The multi-stage purification process involves repeated dispersion, washing, settling, and separation using ultrapure water or deionized water until the washing solution is nearly neutral. The acid solution is nitric acid; In step a, the solid-liquid ratio of the sintered electrolyte powder to the acid-induced solution is 20g:100mL.

2. The method according to claim 1, characterized in that, In step b, the solid-liquid separation includes static sedimentation, decantation, centrifugation, or filtration.

3. The application of the acid-washed proton ceramic electrolyte material with high grain boundary ion conduction prepared according to claim 1, characterized in that, Used to prepare the electrolyte layer for proton ceramic batteries.

Citation Information

Patent Citations

  • Surface modification method and application of garnet electrolyte

    CN114464878A

  • Proton conductor ceramic electrolyte and preparation method thereof

    CN117577911A